Observations of the flow experienced by a track cyclist using velodrome, wind tunnel, and potential flow investigations with an instrumented bicycle. Issue 206 (November 2020) - Fitzgerald, Shaun; Kelso, Richard; Grimshaw, Paul; Warr, Andrew
Abstract: A wind tunnel investigation into the effects of yaw on a track bicycle, ridden by an anatomically-accurate pedalling mannequin, is completed and the results are compared with on-track velodrome data. The results show that there is an amplification effect with a minor bicycle geometric yaw creating a major aerodynamic yaw anterior to the bicycle. The magnitude of this aerodynamic yaw angle amplification increases with increasing front wheel rim depth, with a disc wheel producing the most pronounced effect. A second study into the effects of pedalling legs is also completed with the pedalling mannequin. A 2D potential flow model of the leg movement is created and compared to both wind tunnel data with a pedalling mannequin and velodrome data with a cyclist. The results show a reasonable agreement between the model and both the wind tunnel and velodrome data. There is a large variation in the airflow compared to the freestream that is due to the motion of the legs with a minor difference due to the effect of cadence. The data presented here is useful for bicycle design because it demonstrates and quantifies the aerodynamic influence across different parts of the bicycle. Highlights: The airflow around an instrumented track bicycle is investigated in a velodrome and in a wind tunnel. The front wheel has a large influence on the flow around the whole bicycle. A potential flow model of a cyclist's moving legs is created and compared to experimental data. Results indicate a strong effect of reduced frequency on the flow between the cyclist's legs. Findings can be used as a guide for segmented bicycle design.